Diseño, desarrollo e implementación de una aplicación web para la creación de portafolios electrónicos - Malo Pinza, Frank Carlos (2009)
Currently there are many tools for the creation of electronic portfolios, but one of the most notable weaknesses is that the majority of these systems are not collaborative tools. Namely, they do not exploit the advantages that the web 2.0 has to offer. The tools that allow the use of applications, such as blogs or social networks, do not possess a personalized and usable interface . For these reasons, this paper proposes to design a tool capable to fulfill three basic important points in a portfolio tool: Commit students to the learning content, assist student to acquire critical-thinking and self evaluation skills and document student’s learning, using web 2.0 tools.